WiFi, WiMAX and LTE Multi-hop Mesh Networks : Basic Communication Protocols and Application Areas. - Wei, Hung-Yu.; Rykowski, Jarogniew; Dixit, Sudhir (Chicester : Wiley, 2013)
Wifi, WiMAX, and Cellular Multihop Networks presents an overview of WiFi-based and WiMAX-based multihop relay networks. As the first text to cover IEEE 802.16j multihop hop relay technology, this revolutionary resource explores the latest advances in multi-hop and ad-hoc networking. Not only does this reference provide the technological aspects, but also the applications for the emerging technology and architectural issues. Ranging from introductory material to advanced topics, this guidebook, plus PowerPoint slides, is essential for engineers, researchers, and students interested in.
5.11. MULTICAST, BROADCAST, AND RS GROUPING5.12. RS GROUPING; 5.13. SUMMARY; 6 Wireless Relay Networking with Long Term Evolution (LTE); 6.1. OVERVIEW OF THE LTE RELAY SYSTEM; 6.2. PHYSICAL LAYER FOR LTE RELAY; 6.3. LTE RELAY SYSTEM ARCHITECTURE; 6.4. LTE RELAY SYSTEM DESIGN ISSUES; 6.5. FUTURE DEVELOPMENT IN LTE RELAY; 6.6. SUMMARY; 7 Summary; REFERENCES; INDEX.
Print version record.
Keywords: Ad hoc networks (Computer networks); Wireless LANs; Ad hoc networks (Computer networks); Wireless LANs; Electronic books